TIPOLOGI PEDOGEOMORFIK KEJADIAN LONGSORLAHAN DI PEGUNUNGAN KULONPROGO DAERAH ISTIMEWA YOGYAKARTA INDONESIA - , Kuswaji Dwi Priyono, Drs.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research dissertation at Kulonprogo Mountains aims to: (1) determine the landforms characteristic of landslide occurrence in research areas